User Engangement Pada Perpustakaan dan Pustakawan di Era Ekonomi Digital: Sebuah Narrative Literature Review - Rahayu, Rochani Nani (Ikatan Pustakawan Indonesia, 2023)
Research to find out the methods used to involve users in libraries and librarians, was conducted using the narrative literature review method. Starting with a literature search, the Scopus database was selected, which is the largest database for abstracts, citations, and peer-reviewed scientific literature. A search strategy was carried out using the keywords: